Biometri Organ Reproduksi Bagian Luar dan Karakteristik Ejakulat Anoa (Bubalus sp.) yang Dikoleksi Menggunakan Elektroejakulator Setelah Diinjeksi hCG - Yudi Yudi; T L Yusuf; B Purwantara; D Sajuthi; S Mulyono; J Manansang (Faculty of Animal Science, Bogor Agricultural University, 2009)
This experiment aimed to investigate characteristics of reproductive organ (external parts) of the anoa (Bubalus sp.) and semen characteristics that collected by using electroejaculator after hCG injection, as an initial step on implementation of assisted reproductive techniques. Anoa is Indonesian endemic fauna that included into Appendix I by CITES. Anoa breeding efforts have not succeeded, due to their agressivity, soliter, wildness and monogamous. This experiment was carried out in Ragunan Zoo (Jakarta), Taman Safari Indonesia (Bogor), and Divison of Reproduction, Obstetrics and Gynaecology Faculty of Veterinary Medicine, Bogor Agricultural University (IPB). Biometry of reproductive organ were measured by microcaliper and nylon tape. Semen was collected by electroejaculator, under anesthetized condition. Ejaculate was evaluated macro- and microscopically. The results showed that the reproductive organ was larger as it is getting older. But, it was generally smaller compared to the buffalo's. The characteristics of fresh semen were: volume 1.02±0.28 ml, pH 6.93±0.19, mass movement 0, progressive motility 52.50±18.91%, live-death ratio 67.48±8.24%, concentration 263.33±105.06 billion/mL and total abnormality 31.86±3.72% (primary abnormality 9.52±3.85%, secondary abnormality 22.33±1.46%). The semen qualities were fairly good, even though some parameters showed lower number compared to buffalo's. It is important to improve the collection technique, animal handling and appropriate extender development for semen cryopreservation. Key words: anoa, biometry of external reproductive organ, semen characteristics, electroejaculator